The LAMMER Kinase, LkhA, Affects Aspergillus fumigatus Pathogenicity by Modulating Reproduction and Biosynthesis of Cell Wall PAMPs - Lim, Joo-Yeon; Kim, Yeon Ju; Woo, Seul Ah; Jeong, Jae Wan; Lee, Yu-Ri; Kim, Cheol-Hee; Park, Hee-Moon (Frontiers in Cellular and Infection Microbiology, 2021)
The LAMMER kinase in eukaryotes is a well-conserved dual-specificity kinase. Aspergillus species cause a wide spectrum of diseases called aspergillosis in humans, depending on the underlying immune status of the host, such as allergy, aspergilloma, and invasive aspergillosis. Aspergillus fumigatus is the most common opportunistic fungal pathogen that causes invasive aspergillosis. Although LAMMER kinase has various functions in morphology, development, and cell cycle regulation in yeast and filamentous fungi, its function in A. fumigatus is not known. We performed molecular studies on the function of the A. fumigatus LAMMER kinase, AfLkhA, and reported its involvement in multiple cellular processes, including development and virulence. Deletion of AflkhA resulted in defects in colonial growth, production of conidia, and sexual development. Transcription and genetic analyses indicated that AfLkhA modulates the expression of key developmental regulatory genes. The AflkhA-deletion strain showed increased production of gliotoxins and protease activity. When conidia were challenged with alveolar macrophages, the recognition of conidia by macrophages was increased in the AflkhA-deletion strain, resulting from increased cell wall pathogen-associated molecular patterns. While T cell-deficient zebrafish larvae were significantly susceptible to wild-type A. fumigatus infection, AflkhA-deletion conidia infection reduced host mortality. A. fumigatus AfLkhA is required for the establishment of virulence factors, including conidial production, mycotoxin synthesis, protease activity, and interaction with macrophages, which ultimately affect pathogenicity at the organismal level.